Innovative Mode of English Education Based on Internet - Yan, Juan (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: With the deepening application of cloud computing, mobile Internet, and big data technology in education, China's education informatization presents a new trend of integration and innovation, especially in the areas of resource sharing and interconnection, online and offline integration of teaching and learning, and good management and education governance based on big data, "Internet+Education" will have a systematic change impact on education. It will systematically impact education and open new paths for developing and utilizing English curriculum resources in colleges and universities in the Internet era.OBJECTIVES: To enhance the development level of online education in China and promote the sustainable development of online English education in China; to solve the problems of rigidity and unremarkable innovation in English education mode in colleges and universities and to promote the development of the integration of Internet technology and English teaching, and to improve the level of combining the theory and practice of English online education in China.METHODS: Firstly on the use of literature theoretical research to find the necessity of the Internet's English education innovation model research and adapt to the theoretical model; secondly, through the method of questionnaires and interviews from the teachers and students of two perspectives to study the effect of the Internet-based English education innovation model; finally, the use of empirical methods to validate the level of efficiency of the Internet's English education innovation model.RESULTS: The research on the innovative model of English education based on the Internet is necessary; the result that "Internet+" education can improve the teaching effect can be obtained from both the teachers' and students' perspectives; the empirical method verifies that the efficiency of the innovative model of English education based on the Internet is higher than that of the traditional one.CONCLUSION: Most teachers and students know or have come into contact with online college English course resources, but their understanding could be better. Moreover, they have used them but have yet to have the opportunity to participate in their development, which is related to the level of teachers' and students' professional knowledge and ability and also predicts the growth and utilization of course resources by college English teachers. The comparison of teachers' and students' expectations leads to the conclusion that teachers and students in the studied universities have positive attitudes and high expectations and expect to develop and use more systematic and scientific online English course resources.
Keywords: internet; English education; innovation; educational mode